The Stability of Dentin Surface Biobarrier Consisting of Mesoporous Delivery System on Dentinal Tubule Occlusion and Streptococcus Mutans Biofilm Inhibition - Yu J (Dove Medical Press, 2021)
Jian Yu,* Luyao Yi,* Rui Guo, Jingmei Guo, Hongye Yang, Cui Huang The State Key Laboratory Breeding Base of Basic Science of Stomatology (Hubei-MOST) & Key Laboratory for Oral Biomedicine Ministry of Education, School and Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongye Yang; Cui HuangThe State Key Laboratory Breeding Base of Basic Science of Stomatology (Hubei-MOST) & Key Laboratory for Oral Biomedicine Ministry of Education, School and Hospital of Stomatology, Wuhan University, #237 Luoyu Road, Wuhan, 430079, Hubei Province, People’s Republic of ChinaEmail yanghongye@whu.edu.cn; huangcui@whu.edu.cnBackground: The dentin exposure always leads to dentin hypersensitivity and/or caries. Given the dentin’s tubular structure and low mineralization degree, reestablishing an effective biobarrier to stably protect dentin remains significantly challenging. This study reports a versatile dentin surface biobarrier consisting of a mesoporous silica-based epigallocatechin-3-gallate (EGCG)/nanohydroxyapatite delivery system and evaluates its stability on the dentinal tubule occlusion and the Streptococcus mutans (S. mutans) biofilm inhibition.Materials and Methods: The mesoporous delivery system was fabricated and characterized. Sensitive dentin discs were prepared and randomly allocated to three groups: 1, control group; 2, casein phosphopeptide–amorphous calcium phosphate (CPP–ACP) group; and 3, the mesoporous delivery system group. The dentin permeability, dentinal tubule occlusion, acid and abrasion resistance, and S. mutans biofilm inhibition were determined for 1 week and 1 month. The in vitro release profiles of EGCG, Ca, and P were also monitored.Results: The mesoporous delivery system held the ability to sustainably release EGCG, Ca, and P and could persistently occlude dentinal tubules with acid and abrasion resistance, reduce the dentin permeability, and inhibit the S. mutans biofilm formation for up to 1 month compared with the two other groups. The system provided prolonged stability to combat oral adverse challenges and served as an effective surface biobarrier to protect the exposed dentin.Conclusion: The establishment of the dentin surface biobarrier consisting of a mesoporous delivery system indicates a promising strategy for the prevention and the management of dentin hypersensitivity and caries after enamel loss.Keywords: epigallocatechin-3-gallate, nanohydroxyapatite, mesoporous silica, dentin, biofilm